A Model Study to Unravel the Complexity of Bio‐Oil from Organic Wastes. Issue 1 (22nd December 2016) - Croce, Annamaria; Battistel, Ezio; Chiaberge, Stefano; Spera, Silvia; De Angelis, Francesco; Reale, Samantha
Abstract: Binary and ternary mixtures of cellulose, bovine serum albumin (BSA) and tripalmitin, as biomass reference compounds for carbohydrates, proteins and triglycerides, respectively, were treated under hydrothermal liquefaction (HTL) conditions to describe the main reaction pathways involved in the process of bio‐oil production from municipal organic wastes. Several analytical techniques (elemental analysis, GC–MS, atmospheric‐pressure photo‐ionisation high‐resolution Fourier transform ion cyclotron resonance mass spectrometry, and 13 C cross‐polarisation magic‐angle spinning NMR spectroscopy) were used for the molecular‐level characterisation of the resulting aqueous phase, solid residue and bio‐oil, in particular. The main reaction pathways led to free fatty acids, fatty acid amides, 2, 5‐diketopiperazines and Maillard‐type compounds as the main components of the bio‐oil. The relationship of such compounds to the original components of the biomass was thus determined, which highlights the fate of the heteroatom‐containing molecules in particular. Finally, the molecular composition of the bio‐oils from our reference compounds was matched with that of the bio‐oil from municipal organic waste biomass by comparing their high‐resolution Fourier transform ion cyclotron resonance mass spectra, and we obtained a surprisingly high similarity. Hence, the ternary mixture acts as a reliable biomass model and is a powerful tool to clarify the degradation mechanisms that occur in the biomass under HTL treatment, with the ultimate goal to improve the HTL process itself by modulating the input of the organic starting matter and then the upgrading steps to bio‐fuels. Abstract : Unravelling bio‐oil complexity : The reaction networks involved in the hydrothermal liquefaction treatment (HTL) of a municipal organic waste biomass are investigated in depth and reconstructed by characterizing the products derived from the treatment of binary and ternary mixtures of reference compounds that comprise the three main components of organic waste biomasses (carbohydrates, proteins, and lipids).